Investigation of the splitting tensile performance of Rock-Filled Concrete based on mesoscopic modeling: Effects of the interfacial transition zone and rockfill characteristics - Qian Li; Ning Liu; XiaoLing Tang; Peng Chen; YouBin Li; Tao Yang (PLoS ONE, 2026)
Rock-filled concrete (RFC) is a three-phase heterogeneous composite composed of large-size rockfill, self-compacting concrete (SCC), and the interfacial transition zone (ITZ) between them. Its mechanical performance is jointly affected by the rockfill skeleton effect and the properties of the ITZ. Existing studies still provide insufficient understanding of how interfacial properties and rockfill characteristics influence the splitting tensile performance and damage evolution mechanism of RFC. In this study, splitting tensile tests of RFC were conducted based on an actual engineering project, and an engineering-scale three-dimensional mesoscopic finite element model was established based on the experimental results. The effects of ITZ strength, rockfill strength, and rockfill particle size on the splitting tensile mechanical response, damage evolution process, and failure morphology of RFC were investigated. The results show that when σ ITZ ∕ σ scc increased from 0.2 to 1.0, the splitting tensile strength of RFC increased by 36.75%; when σ Rock ∕ σ scc increased from 1.0 to 5.0, the splitting tensile strength increased by 39.65%. The splitting tensile strength of RFC increased with increasing ITZ strength and rockfill strength and gradually approached saturation, with threshold values of σ ITZ ∕ σ scc = 0.8 and σ Rock ∕ σ scc = 4.0, respectively. The influence of rockfill particle size on splitting tensile strength showed a trend of first increasing and then decreasing. Compared with a single particle size distribution, a graded particle size distribution improved the rockfill skeleton structure and more effectively enhanced the splitting tensile performance of RFC. Overall, improving ITZ quality and adopting a properly graded rockfill particle size distribution are important approaches for enhancing the splitting tensile performance of RFC, and the findings provide a theoretical basis for RFC material design and engineering applications.